FEA Analysis for Scissor Lifting Table - et. al., V.Giridharan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main goal of the project is weight analysis of scissor lifting table in the ware house, the scissor lifting table is a common device for all kind of peoples, we go to do the structural analysis of the scissor lifting table with the various human weights scissor lifting table modelled in Solid works software and structural analysis of human weights 50kg, 75kg, 100kg and 125kg done in ANSYS workbench software Scissor-type systems are frequently used as